On the informational efficiency of Saudi exchange-traded funds listed at home and away from home - Nassar S. Al-Nassar (Cogent Economics & Finance, 2021)
This study compares the pricing efficiency of two domestic exchange-traded funds (ETFs) (i.e., Falcom 30 and HSBC 20) listed on the Saudi stock exchange (i.e., Tadawul), as well as an international ETF (i.e., iShares MSCI Saudi Arabia) listed on the NYSE, by examining the extent and properties of the deviations of their prices from their net asset values (NAVs), and whether these deviations persist and vary over time. The results show that the deviations of the market prices of all of the ETFs are significantly large and persist for at least three days. It is shown that the standard deviation of the premiums/discounts based on the dyna model are large, particularly for the domestic funds. The premiums/discounts appear to be exacerbated during the periods of market turbulence. The results from cointegration analysis support the existence of a long-run relationship between the prices and the NAVs of the three ETFs. However, the ETFs' prices do not fully reflect the fundamental information contained in the underlying basket of the stocks in either the long run or the short run. Furthermore, the adjustment toward the long-run relationship seems to be quite slow, albeit apparently faster in the case of iShares MSCI Saudi Arabia. The restrictions on short selling, the concentration of authorized market participants, the increased cost for the creation and redemption of the ETF shares, and the lack of an active secondary market for the ETF shares can create major limits to arbitrage, thereby impeding efficiency in the market.
Keywords: G12; G15; G23; 330; arbitrage; exchange traded funds; pricing efficiency; Saudi market